Effects of continuous cropping Jiashi muskmelon on rhizosphere microbial community - Wang, Jilian; Li, Mingyuan; Zhou, Qian; Zhang, Tian (Frontiers in Microbiology, 2023)
The continuous cropping of crops can result in the deterioration of the soil environment and cause a decline in plant health and yield, which complicates agricultural production. However, the effects of continuous melon cropping on rhizospheric microbial communities remain poorly understood. In this study, high-throughput absolute quantification 16S rRNA gene amplicon sequencing was employed to analyse the bacterial community structure of greenhouse rhizosphere soil from Jiashi muskmelon replanted for 0, 1, 2, and 3 years (CK, 1a, 2a, and 3a, respectively). The results showed that long-term continuous cropping caused significant changes in soil physicochemical properties. The bacterial absolute abundances increased, but the bacterial community richness and diversity were significantly lost (p < 0.05). The composition of bacterial community was more similar after 2 and 3 years of continuous cropping. The longer the continuous cropping years were, the greater the shift in the bacterial diversity and abundance. Analysis of potential functional components revealed that different bacterial groups were enriched in different continuous cropping years. The significant reduction of the taxa associated with nitrate reduction may be responsible for the loss of soil nitrogen in continuous cropping soil. In summary, continuous cropping had a significant impact on the bacterial community structure of Jiashi muskmelon rhizospheric soil, and these results will provide a reference for soil management and scientific fertilization of melon and other crops under a continuous cropping regime.